ISOTOPIC CHARACTERIZATION OF ORGANIC MATERIALS LEACHED FROM LEAVES IN WATER OF MUNDARING WEIR DAM - Markus Heryanto Langsa (Universitas Gadjah Mada, 2010)
This study examined the organic constituents aquatically leached from leaf components of two tree species (wandoo eucalyptus and pinus radiate). In particular this study aimed to assess the stable isotope composition behaviour of dissolved organic carbon (DOC) from the residue leaves after leaching over five months. The changes in the stable carbon and nitrogen isotope compositions of the leached leaves materials were investigated using an elemental analyzer-isotope ratio mass spectrometry (EA-irMS). The stable isotope compositions were found to vary according to microbially-mediated alteration and decomposition. The average d13C content of the raw plant elements was consistent with the d13C values of terrestrial plants using a C3 photosynthetic pathway. The isotope compositions of leached materials of wandoo eucalyptus fresh leaf were continually depleted in d13C over the leaching period of three months. These variations correlated well with its DOC profile. Changes in d13C values may also relate to the differential leaching of the macromolecular precursors of the original material. Lignin, for example, has a typically low d13C and probably contributed to the decrease of d13C in residue of the plant materials.